Somatic Stem Cells in the Myometrium and in Myomas - Maruyama, Tetsuo; Ono, Masanori; Yoshimura, Yasunori (Seminars in Reproductive Medicine, 2013)
The human uterus mainly consists of two layers: an inner endometrium and an outer layer, the myometrium, made of smooth muscle. The uterus is characterized by its unique capacity for regeneration. This capacity permits cyclical regeneration and remodeling of the tissue over the course of a woman's reproductive life. During each menstrual cycle, the endometrium regenerates, and the uterus enlarges to make room for fetal growth. This cyclic physiologic pattern suggests that myometrial stem/progenitor cells are present in the tissue and play a role in myometrial functions. Our group (and others) recently characterized and isolated putative stem/progenitor cells in the myometrium. These findings are permitting a better understanding of myometrial physiology and pathology. We review current studies of myometrial stem/progenitor cells and suggestions that, in combination with hypoxia, these cells may contribute to uterine remodeling during pregnancy and the formation of myomas.
Keywords: somatic stem cells; myomas (fibroids); hypoxia; pregnancy; myometrium